2015
DOI: 10.3201/eid2109.150508
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Epidemiology and Improving Surveillance of Infections Associated with Health Care, United States

Abstract: This national resource provides much-needed data on pathogens, infections, and antimicrobial drug use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…No signs or symptoms of disease were reported, indicating probable asymptomatic bacteriuria. The isolate was submitted to the CDC as part of the Emerging Infections Program Multi-site Gramnegative Surveillance Initiative (MuGSI), (13), which has conducted active populationand laboratory-based surveillance for carbapenem-resistant pathogens since 2012.…”
mentioning
confidence: 99%
“…No signs or symptoms of disease were reported, indicating probable asymptomatic bacteriuria. The isolate was submitted to the CDC as part of the Emerging Infections Program Multi-site Gramnegative Surveillance Initiative (MuGSI), (13), which has conducted active populationand laboratory-based surveillance for carbapenem-resistant pathogens since 2012.…”
mentioning
confidence: 99%
“…In 2011, the Centers for Disease Control and Prevention identified via a prevalence survey that 4 percent of hospitalized patients had an HAI. 2,3 The same survey repeated in 2015 found that 3.2 percent of patients had an HAI. 2 Patients in the 2015 survey also had a 16 percent lower risk of acquiring an HAI than patients surveyed in 2011.…”
Section: Prevalence Datamentioning
confidence: 95%
“…Infection with C. difficile, a major focus for hospitalized patients in the general population (24)(25)(26), was also specifically examined in the Peer report (12). Admissions for C. difficile infections among dialysis patients within the first 12 months of initiation increased nearly 44% between 2004 and 2012, from approximately 1.6 (95% CI, 1.5 to 1.7) to 2.3 (95% CI, 2.1 to 2.4) admissions per 100 patient-years.…”
Section: Novel Disease Findingsmentioning
confidence: 99%